Numerical Study of the Unsteady Aerodynamic Performance of Two Maglev Trains Passing Each Other in Open Air Using Different Turbulence Models - Xianli Li; Siniša Krajnovic; Dan Zhou (Applied Sciences, 2021)
The strong change in the flow fields around two maglev trains (MTs) passing each other in open air may affect their manoeuvrability and passengers’ comfort. In this study, we evaluated the aerodynamic performance of two MTs passing each other via shear stress transport (SST) k–ω model and improved delayed detached eddy simulations based on the Spalart–Allmaras model (SA−IDDES) and the SST k–ω model (SST−IDDES). The accuracy of the numerical simulation method was verified using experimental data acquired from a moving model test. The results showed that the difference in the amplitude of the transient pressure obtained with the different turbulence models was less than 5%. The wake vortex structures on the intersection side were found to interact, and their intensity consequently decreased. The SST−IDDES model produced smaller-scale vortices than the SA−IDDES model, particularly in the near-wake region. There were large differences in the drag and lift forces obtained using the different turbulence models. Among them, the lift force of the tail car was more sensitive to the turbulence model, and its maximum value obtained with the SST−IDDES model was 11% larger than that obtained with the SA−IDDES model.